2014
DOI: 10.1111/psyp.12257
|View full text |Cite
|
Sign up to set email alerts
|

Segmental and suprasegmental features in speech perception inCantonese‐speaking second graders: AnERPstudy

Abstract: Using a multiple-deviant oddball paradigm, this study examined second graders' brain responses to Cantonese speech. We aimed to address the question of whether a change in a consonant or lexical tone could be automatically detected by children. We measured auditory mismatch responses to place of articulation and voice onset time (VOT), reflecting segmental perception, as well as Cantonese lexical tones including level tone and contour tone, reflecting suprasegmental perception. The data showed that robust mism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…There is a large body of MMN research on adult tonal processing in both Mandarin (Bidelman & Chung, 2015; Chandrasekaran, Krishnan, & Gandour, 2007, 2009; Chandrasekaran, Gandour, & Krishnan, 2007; Gu et al, 2012; Hsu, Lin, Hsu, & Lee, 2014; Li & Chen, 2015; Lu, Wayland, & Kaan, 2015; Luo et al, 2006; Ren, Yang, & Li, 2009; Wang, Gu, He, Chen, & Chen, 2012; Xi et al, 2010; H. Y. Zheng et al, 2014; among others) and Cantonese (Gu, Zhang, Hu, & Zhao, 2013; Jia, Tsang, Huang, & Chen, 2015; Law, Fung, & Kung, 2013a,b; Tong et al, 2014; Tsang, Jia, Huang, & Chen, 2011; H. Y. Zheng et al, 2014; among others).…”
Section: Mandarin Tones and The Mmnmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of MMN research on adult tonal processing in both Mandarin (Bidelman & Chung, 2015; Chandrasekaran, Krishnan, & Gandour, 2007, 2009; Chandrasekaran, Gandour, & Krishnan, 2007; Gu et al, 2012; Hsu, Lin, Hsu, & Lee, 2014; Li & Chen, 2015; Lu, Wayland, & Kaan, 2015; Luo et al, 2006; Ren, Yang, & Li, 2009; Wang, Gu, He, Chen, & Chen, 2012; Xi et al, 2010; H. Y. Zheng et al, 2014; among others) and Cantonese (Gu, Zhang, Hu, & Zhao, 2013; Jia, Tsang, Huang, & Chen, 2015; Law, Fung, & Kung, 2013a,b; Tong et al, 2014; Tsang, Jia, Huang, & Chen, 2011; H. Y. Zheng et al, 2014; among others).…”
Section: Mandarin Tones and The Mmnmentioning
confidence: 99%
“…nan, & Gandour, 2007nan, & Gandour, , 2009Hsu, Lin, Hsu, & Lee, 2014;Li & Chen, 2015;Lu, Wayland, & Kaan, 2015;Luo et al, 2006;Ren, Yang, & Li, 2009;Xi et al, 2010;H. Y. Zheng et al, 2014; among others) and Cantonese(Gu, Zhang, Hu, & Zhao, 2013;Jia, Tsang, Huang, & Chen, 2015; Law, Fung, & Kung, 2013a,b;Tong et al, 2014;Tsang, Jia, Huang, & Chen, 2011;H. Y. Zheng et al, 2014; among others).…”
mentioning
confidence: 99%
“…2) Differences between stimuli. The magnitude of the difference between the standard and deviant stimuli may induce different polarity of the difference wave [12, 1516, 1819]. Additionally, this study showed that the age at cochlear implantation was one influencing factor of the MMR polarity in children.…”
Section: Discussionmentioning
confidence: 82%
“…The modified TRACE model, which tries to illustrate the perception process of tonal languages, holds that the mental representations of tonemes and phonemes are stored separately and are processed partially independently within their own pathways (Ye & Connine, 1999). However, a batch of studies (e.g., Choi et al, 2017;Shuai & Malins, 2017;Tong et al, 2014) observe similar processing patterns for lexical tones and vowels, pointing to the simultaneous access of these cues. The present study, which finds different time courses for lexical tone normalization and vowel normalization, supports the concept of separate processing of lexical tones and vowels in tonal languages.…”
Section: The Normalization Of Lexical Tones and Vowels In The Percept...mentioning
confidence: 99%